Family-Based Tutoring Programs For Mental Retardation Children With Mild Disabilities In The Covid-19 Era - Mega Sri Warahmah; Budi Susetyo (Edumaspul: Jurnal Pendidikan, 2023)
Researchers found problems in SLB BC YPNI Pameungpeuk Regency during the current covid-19 pandemic. Namely, there is no family-based tutoring program for children with mild mental retardation in the covid-19 era. Therefore, researchers conducted a study at SLB BC YPNI Pameungpeuk Bandung Regency regarding a family-based tutoring program for children with mild mental retardation in the covid-19 era. The purpose of this study is to make a family-based tutoring program for children with mild disabilities in the covid-19 era feasible. The research method used is design based research (DBR) method with qualitative approach. Data collection used is observation, interview, documentation and validation. The results of this study are family-based tutoring programs for children with mild disabilities in the covid-19 era in the form of programs. This follow-up of the family-based tutoring program for children with mild disabilities in the covid-19 era can be used by the school and can also be used as a basis for further research by subsequent researchers. The researcher hopes that the family-based tutoring program for children with mild mental retardation in the covid-19 era can be used in SLB BC YPNI Pameungpeuk Bandung Regency as a research site but can also be used by other schools that have the same problems as the problems at the research site.